Perancangan Knowledge Management System menggunakan Tools "Book Review": Studi Kasus pada Universitas Bina Nusantara - Karto Iskandar (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The role of knowledge in developing and maintaining an organization has been strongly regarded as a very important asset. Bina Nusantara University is one of the universities that is aware of the importance of book as main knowledge media in the learning process. Reviewing books and sharing the results can be a major resource to perform maintenance on knowledge and accelerate the learning process. A problem that occurs in Bina Nusantara University is no application to do Book Reviews. There are no tools that facilitate discussion between book reviewer and book review reader. The purpose of this research is to design features of Book Review on Knowledge Management System (KMS) in Bina Nusantara University. It is expected that book review features are useful for faculty members and staffs in doing book reviews. The methodology used in this study is literature study and design a KMS application using Microsoft SharePoint 2010 technology. Conclusion of this research is the application of KMS Book Review in Bina Nusantara University can encourage book reviewers and facilitate book review readers to discuss and interact more optimally.